Correlation of Serum Androgens and Pituitary Hormone Levels with Serum PSA Less Than 2.5 NG/ML - Sofikerim, Mustafa (ScientificWorldJournal, 2007)
The aim of this clinical study was to determine whether there is a relationship between total serum testosterone, free testosterone, FSH (Follicle-Stimulating Hormone), LH (Luteinizing Hormone) and serum prostate specific antigen (PSA) levels. We postulated that such a correlation existed then the use of hormone specific reference ranges might enhance the usefullness of PSA concentrations <2.5 ng/mL as a marker for prostate cancer. Prior to digital rectal examination, serum was obtained from all patients between 8.30-10:00 AM for hormone and PSA concentrations. The study was performed on 210 male patients >40 years of age visiting our urology outpatient clinics. PSA was correlated to age (r = 0.23, p = 0.019), but there none between serum testosterone and age. No significant correlation was noted between testosterone or free testosterone and serum PSA levels, and none between serum FSH or LH and PSA. In age specific reference groups (41-49; 50-59; 60-69 years), we found no significant correlation between PSA and hormone concentrations. In this population of eugonadal men with serum PSA values less than 2.5 ng/ml, serum androgens and pituitary hormones do not appear to correlate with serum PSA.